KHAWARIJISME: PERGULATAN POLITIK SEKTARIAN DALAM BINGKAI WACANA AGAMA - Fahmy Farid Purnama (UIN Raden Mas Said Surakarta, 2016)
As a sect that emerged since attahkim, Khawarij represents a portrait of an affair relation between power and religious discourse (theological discourse). The doctrine of takfir and other religious destructive actions are pragmatically emerged from the way of the sect in reading the religious discourses which are literal and simplistic. The politics and ideology of sectarian practiced by Khawarij which are captured in the socio-political and history of Islam has become a negative precedent for the next Muslim’s generation. Various destructive actions, by making the religious discourse as an instrument of power, not only disrupt the political stability but also distort the logical thinking and consciousness of Muslims, and even continued to be passed on to subsequent generations. Khawarij became symptom of the radicalization of religious discourse in the realm of contemporary politics that is often termed as neo-Khawarijism.